Optimalisasi Jarak Tanam Terhadap Peningkatan Produksi Hanjeli Pulut (Coix lacrima-jobi L.) pada Lahan Tidur - Nugraha Ramadhan; Rachmad Hersi Martinsyah; Indra Dwipa (Jurnal Agroekoteknologi, 2023)
Utilizing idle land as agricultural land is one option that can be pursued to support national food security and independence. Indonesia has various types of alternative food commodities that have the potential to be developed on nutrient-poor land, one of which is hanjeli. Technical cultivation is needed to increase the growth and yield of hanjeli on sub-optimal land. This study aims to determine the best planting distance to increase hanjeli production on idle land. The research was conducted from October 2020 - March 2021 in Limau Manis, Padang City, West Sumatra. The materials used in this study were rice cultivar hanjeli seeds, manure (20 tons/ha) and NPK fertilizer (200 kg/ha). The experimental design used was Randomized Group Design with 3 groups and consisted of 8 plant spacing treatments (40 x 40 cm, 50 x 40 cm, 50 x 50, 50 x 60 cm, 50 x 70 cm, 50 x 80 cm, 50 x 90 cm, and 50 x 100 cm). Observation data were analyzed statistically to determine the influential treatment using the F test at the 5% level and significantly different data were tested using the Duncan’s Multiple Range Test at the 5% level. It was concluded that the spacing of 50 x 70 cm, 50 x 80 cm, 50 x 90 cm and 50 x 100 cm gave the best effect on the number of total tillers/plant, the number of productive tillers/plant, the number of seeds/plant, the percentage of filled seeds, the weight of filled seeds/plant. As for productivity, the spacing of 50 x 80 cm gave the best results.